Glasgow prognostic score predicts survival in patients with unresectable hepatocellular carcinoma treated with lenvatinib: a multicenter analysis. Issue 8 (29th June 2022) - Tada, Toshifumi; Kumada, Takashi; Hiraoka, Atsushi; Hirooka, Masashi; Kariyama, Kazuya; Tani, Joji; Atsukawa, Masanori; Takaguchi, Koichi; Itobayashi, Ei; Fukunishi, Shinya; Tsuji, Kunihiko; Ishikawa, Toru; et al.
Abstract : Objective: The use of Glasgow prognostic score (GPS), calculated using the serum C-reactive protein and albumin levels, to predict the outcomes of patients with unresectable hepatocellular carcinoma (HCC) treated with lenvatinib was investigated in this study. Methods: A total of 508 patients with Child-Pugh class A HCC treated with lenvatinib were included in this study. Results: The median overall and progression-free survivals were 20.4 months [95% confidence interval (CI), 17.7–23.2 months] and 7.5 months (95% CI, 6.8–8.5 months), respectively. The median overall survivals of patients with a GPS of 0, 1, and 2 were 28.5, 16.0, and 9.1 months, respectively ( P < 0.001). When adjusted for age, sex, performance status, etiology, α-fetoprotein, macroscopic vascular invasion, extrahepatic spread, history of sorafenib therapy, and GPS, a GPS of 1 [hazard ratio (HR), 1.664; 95% CI, 1.258–2.201; P < 0.001] and a GPS of 2 (HR, 2.664; 95% CI, 1.861–3.813; P < 0.001) were found to be independently associated with overall survival. The median progression-free survivals of patients with a GPS of 0, 1, and 2 were 8.8, 6.8, and 3.8 months, respectively ( P < 0.001). When adjusted for the same factors of overall survival, a GPS of 2 (HR, 2.010; 95% CI, 1.452–2.784; P < 0.001) was found to be independently associated with progression-free survival. As the albumin–bilirubin with tumor node metastasis score increased, the proportion of patients with a GPS of 1 or 2 increased ( P < 0.001). Conclusions: GPS can be used to predict survival in patients with unresectable HCC who were treated with lenvatinib.